Cardiovascular Effects and Pattern of Use of Antineoplastic Therapies in Female Breast Cancer Patients - Sophie, Hamel (Université d'Ottawa / University of Ottawa, 2014)
Cancer survivors are at greater risk of cardiovascular diseases in comparison to the general population. Cardiovascular disorders are among the most prominent comorbidities in breast cancer patients. In order to gain a better understanding of the prescribing practices and cardiovascular risks associated with oncology drugs, this thesis encompasses a detailed review of the molecular and physiological mechanisms leading to drug‐induced cardiotoxicity and an evaluation of the cardiovascular risks associated with cancer drug therapies. Using a nested case‐control design, we evaluated whether these cancer drugs were associated with adverse cardiovascular outcomes under real‐world conditions of use. Although only few oncology drugs are indicated for breast cancer treatment, we were interested in prescribing practices and whether breast cancer treatments are restricted to labelled indications. The characterization of prescribing practices provides insights on the range of antineoplastic agents that should be considered in the evaluation of treatmentrelated adverse reactions such as cardiotoxicity. We found that selective estrogen receptor modulators demonstrated a better safety profile than aromatase inhibitors based on their mechanism of action on the cardiovascular system. These observations were corroborated by our findings from logistic regression analyses where aromatase inhibitors were associated with a higher risk of heart failure in a heterogeneous population of breast cancer patients. We reported that off‐label prescribing is common strategy in breast cancer treatment. While this practice tends to be associated with specific socio‐demographic and disease characteristics, the majority of off-label encounters are evidence‐based decisions. Because these off‐label treatments have their own inherent safety profiles, a comprehensive approach, covering all antineoplastic agents administered should be adopted in the evaluation of breast cancer treatment-induced cardiotoxicity. Careful monitoring of patients is crucial for the early detection of warning signs of cardiotoxicity to prevent long‐term deleterious effects. The information contained in this thesis provides useful considerations for the prospective surveillance of cancer drug‐induced cardiac events. These findings point to the need for a multi‐disciplinary approach to facilitate the rapid diagnosis and treatment of cardiac complications secondary to cancer therapy and to ensure that treatment decisions will maximize tumor response while minimizing adverse outcomes.
Keywords: Breast cancer; Pharmacovigilance